Gut Microbiota-Derived Metabolites in the Development of Diseases - Guangyu Shen; Jing Wu; Bang-Ce Ye; Nan Qi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Gut microbiota is increasingly recognized as a metabolic organ essential for human health. Compelling evidences show a variety set of links between diets and gut microbial homeostasis. Changes in gut microbial flora would probably contribute to the development of certain diseases such as diabetes, heart disease, allergy, and psychiatric diseases. In addition to the composition of gut microbiota, the metabolites derived from gut microbiota have emerged as a pivotal regulator in diseases development. Since high-fat and high-protein diets substantially affect the gut microbial ecology and human health, the current review summarizes the gut microbiota-derived metabolites such as short-chain fatty acids (SCFAs), amino acids, and their derivatives and highlights the mechanisms underlying the host responses to these bioactive substances.